Fiber optic sensor based on lateral offset displacement for water quality analysis in agricultural applications - Haroon, Hazura; Azman, Noor Erina; Idris@Othman, Siti Khadijah; Hanim, Abdul Razak; Mohd Zain, Anis Suhaila; Salehuddin, Fauziyah; Othman, Maisara (Wydawnictwo SIGMA-NOT, 2023)
In this study, we developed a fiber optic sensor based on a lateral offset displacement to evaluate the water quality of a hydroponic farming system. The fiber is set up in lateral offset SM-SM fiber mode. The fiber core has been spliced at a variety offset lengths, which serve as a sensing region of the fiber sensor towards the hydroponic crop system's water quality, including pH and temperature. Upon completion, the highest sensitivity was achieved by fiber optic sensor with an offset distance of 18.72 µm, with 0.1972 dBm/pH and 0.2863 dBm/°C for pH and temperature measurements, respectively.